Analisis Bagi Hasil antara Pemilik Lahan dan Petani Padi dalam Perspektif Ekonomi Syariah di Desa Sipi Kecamatan Sirenja - Safinatunnajah Safinatunnajah; Nurul Inayah; Ratih Erisnawati (Jurnal Inovasi Ekonomi Syariah dan Akuntansi, 2026)
This study examines the implementation of the profit-sharing system between landowners and rice farmers in Sipi Village, Sirenja District, and evaluates its compatibility with Islamic economic principles. The study is motivated by the longstanding practice of agricultural profit-sharing conducted through verbal agreements without written contracts. A qualitative field research approach was employed, with primary data collected through observation, interviews, and documentation involving landowners, tenant farmers, and related parties. The data were analyzed through data reduction, data presentation, and conclusion drawing. The findings show that the profit-sharing arrangement allocates 20% of the harvest profits to landowners and 80% to tenant farmers. This distribution is based on the fact that tenant farmers bear all production costs and are fully responsible for managing the agricultural process. From the perspective of Islamic economics, the practice generally complies with sharia principles, including justice, mutual consent, honesty, trustworthiness, balance, and the pursuit of blessings in cooperation. However, the use of oral agreements may create uncertainty regarding the rights and obligations of both parties. Therefore, clearer and preferably written contracts are needed to prevent future disputes and ensure fairness, legal protection, mutual benefit, and the welfare of all parties involved.